Moral and Spiritual Recovery Program (MSRP): A Gender-Responsive Action Addressing the Different Challenges Faced by the Students - Palanas, Victorina; Palanas, Dexter (JPAIR Multidisciplinary Research, 2023)
The current youth landscape in the Philippines is marked by moral ambiguity and apathy towards spiritual and developmental issues. This study delves into the impact of moral and spiritual recovery programs on students at School A. The objective is to address their unique challenges and to identify how the Moral and Spiritual Recovery Program (MSRP) affects individual behavior in terms of Maka-Diyos (Godly), Makatao (Humane), Makakalikasan (Nature Lover), and Makabansa (Patrioticas perceived by teachers, to determine the themes that emerge from the challenges students face, identify the MSRP contribution to their personal growth, and to determine the program that influences the students’ moral and spiritual aspects. Employing a Mixed-Method Research Design utilizing semi-structured interviews with 11 participants and surveys 1,350 participants to explore the role of MSRP in Values Formation at School A. The program transformed the classroom into a space for nurturing self-regulated learners who actively participate, comply with rules, and respect regulations. Three themes drove students’ changing priorities. These are family-centeredness, engagement in various activities, and perception of related factors. Key challenges included time management, depression, and self-analysis issues, with coping strategies like faith and religiosity. Students’ transformative strategies centered on respect and integrity. Moreover, positive behavioral outcomes were observed not only during the MSRP but also during regular class hours. In conclusion, the study highlights the need to update the MSRP and align it with sustainability goals, addressing criticisms and making it more transparent in its current application.